FINANCIAL INFORMATION WITH THE MODERATION OF FIRM SIZE ON THE STOCK PRICE OF LQ45 ISSUERS - Alfonsa Dian Sumarna; Putri Nadya Agustini (Jurnal Akuntansi, 2022)
The stock price is an important factor and must be considered by investors because stock price shows the performance of the company. The stock price also shows the value of a company and is an appropriate index for the effectiveness of the company. Companies that included on category LQ45 (Liquid 45) are the fourty-five dominate listed companies in the Indonesia Stock Exchange. LQ45’s stock price is relatively stable compared to the other companies, even during the current pandemic. This study aims to find empirical evidence regarding the factors that influence and moderate the stock price of LQ45. The independent variables were Price Book Value (PBV), Price Earnings Ratio (PER), profitability proxied by Net Profit Margin (NPM), Debt Equity Ratio (DER) and firm size as moderating variable. This quantitative research uses purposive sampling technique and EViews 9 for data processing. This study examines the partial influence (t-test), simultaneous influence (F-test), and moderating interaction (Moderated Regression Analysis/ MRA). The results of the partial test found that PBV, PER, NPM had some significant influence and DER had an insignificant influence to stock price. For simultaneous result, all independent variables have a significant influence on the stock price. Meanwhile, the results of the MRA found that firm size did not moderate (not a moderating variable) for the influence of the independent variables to the stock price.